Electronic Spreadsheet Tools for Semi- Rigid Frames - Ackroyd, Michael H. (Engineering Journal, 1990)
This paper describes a personal computer software tool for automating the analysis computations for semi-rigid steel frames. The computations are based partly on a design procedure proposed earlier by the author and partly on approximate modeling techniques developed for flexiblyconnected building frames. The computations are implemented in an electronic spreadsheet providing a fully interactive design medium that can be readily accessed by office practitioners.